2021
DOI: 10.1038/s41598-021-89310-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of inflammasome genes associated with pediatric acute lymphoblastic leukemia and clinical prognosis in the Brazilian Amazon

Abstract: The immune system plays an important role in the control of cancer development. To investigate the possible association of inflammasome genes to childhood leukemia we performed a case-control study with 158 patients with acute lymphoblastic leukemia and 192 healthy individuals. The IL1B and IL18 genetic polymorphisms were genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and NLRP1, NLRP3 and P2RX7 were genotyped using Real Time quantitative PCR (qPCR). The IL1B C/T rs19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…As for malignancies of lymphoid origin, CASP1 and NLRP3 showed significantly higher expression in glucocorticoid-resistant primary leukemia cells from patients diagnosed with acute lymphoblastic (ALL) compared to cells sensitive to glucocorticoids [218]. Furthermore, certain CARD8 SNPs in adults and IL-1β SNPs in children were correlated to increased susceptibility for ALL development [219,220]. mRNA expression in NLRP3 and caspase-1 was significantly downregulated in patients with newly diagnosed MM, while NLRP3 mRNA levels negatively correlated with β2-microglobulin levels and BM plasma cell infiltration, features characterizing poor prognosis and more progressed disease.…”
Section: Discussionmentioning
confidence: 99%
“…As for malignancies of lymphoid origin, CASP1 and NLRP3 showed significantly higher expression in glucocorticoid-resistant primary leukemia cells from patients diagnosed with acute lymphoblastic (ALL) compared to cells sensitive to glucocorticoids [218]. Furthermore, certain CARD8 SNPs in adults and IL-1β SNPs in children were correlated to increased susceptibility for ALL development [219,220]. mRNA expression in NLRP3 and caspase-1 was significantly downregulated in patients with newly diagnosed MM, while NLRP3 mRNA levels negatively correlated with β2-microglobulin levels and BM plasma cell infiltration, features characterizing poor prognosis and more progressed disease.…”
Section: Discussionmentioning
confidence: 99%
“…In either in vitro or in vivo experiments, administration of NLRP3 inhibitors caused amelioration of the disease burden in AML, DLBCL, GvHD, multiple myeloma, and sickle cell anemia [ 25 , 36 , 40 , 61 , 67 ]. Moreover, specific gene variants of the NLRP3 inflammasome were correlated with a susceptibility to developing lymphomas, ALL, CML, and possibly MM [ 24 , 38 , 45 , 47 , 48 ]. Altogether, these results show the potentially universal role of the NLRP3 in the pathogenesis of hematological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As glucocorticoids are commonly prescribed medications, these findings are likely to impact resistance management in the future. Additionally, analysis of inflammasome-related genes revealed that IL-1β SNPs in pediatric patients and CARD8 SNPs in adult patients could be potential markers for ALL development susceptibility [ 47 , 48 ].…”
Section: Leukemiasmentioning
confidence: 99%
“…In this study, we used the Updated Guidance on the Reporting of Race and Ethnicityin Medical and Science Journals 53 . Infectious comorbidities were considered infections that serologically tested as IgG + and IgM + (cytomegalovirus, toxoplasmosis, rubella, varicella and parasitic diseases, among others) according to ALVES et al (2021) 54 , and pancreatitis, hemorrhage, and sepsis were considered as “Others”. As the relapse criterion, patients who relapsed after induction therapy (35th day of treatment from Grupo Brasileiro de Tratamento das Leucemias Infantis [GBTLI] 2009 protocol) 55 were included and, for death, patients who died within 5 years were included.…”
Section: Methodsmentioning
confidence: 99%